Polymorphism and Phase-Transition Thermodynamic Properties of Phenazone (Antipyrine) - Dmitrii N. Bolmatenkov; Ilyas I. Nizamov; Andrey A. Sokolov; Airat A. Notfullin; Boris N. Solomonov; Mikhail I. Yagofarov (Molecules)
In this work, detailed information on the phase-transition thermodynamics of the analgesic and antipyretic drug phenazone, also known as antipyrine, is reported. It was found that the compound forms two polymorphs. Fusion thermodynamics of both forms was studied between 298.15 K and Tm using the combination of differential scanning calorimetry and solution calorimetry. The vapor pressures above crystalline and liquid phenazone were measured for the first time using thermogravimetry—fast scanning calorimetry technique. These studies were complemented by computation of the ideal gas entropy and heat capacity and by measurements of the condensed phase heat capacities. On the basis of experiments performed, we derived sublimation and vaporization enthalpies and vapor pressure above liquid and both crystalline modifications of phenazone in a wide range of temperatures.